Collaboration in multi-tier supply chains for reducing empty running: a case study in the UK retail sector. Issue 3 (4th March 2022) - Venegas Vallejos, Melissa; Matopoulos, Aristides; Greasley, Andrew
ABSTRACT: This research aims to explore ways to improve transport efficiency in retail multi-tier supply chains by integrating raw material sourcing of suppliers into the transport network. The performance of the proposed scenario is assessed using a discrete-event simulation (DES) model that includes the additional pick-up and drop-off points of an extended transport network. The results suggest an improvement in the transport network efficiency, evidenced in the reduction of empty running levels and costs. This study supports the idea that the integration of raw material sourcing of suppliers into a retailer's transport network can bring significant benefits.